2020
DOI: 10.3389/fpsyg.2019.02934
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic Utility and Psychometric Properties of the Beck Depression Inventory-II Among Korean Adults

Abstract: The Beck Depression Inventory-II (BDI-II) is one of the most widely used depression assessment tools in Korea. However, the psychometric properties and diagnostic cutoff point of the official Korean version of the BDI-II have not yet been reported. This study aims to clarify the psychometric properties and diagnostic utility of the Korean BDI-II. A total of 1,145 clinical and non-clinical Korean adults participated in this study. The BDI-II showed a high level of internal consistency and high correlations with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
34
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(38 citation statements)
references
References 42 publications
4
34
0
Order By: Relevance
“…Our results are in line with the prior studies. 15,19,26 In accordance with earlier studies, 24,30,51 our results revealed that BDI-II has a good sensitivity and specificity as well as validity and reliability to diagnose depression among cancer patients.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Our results are in line with the prior studies. 15,19,26 In accordance with earlier studies, 24,30,51 our results revealed that BDI-II has a good sensitivity and specificity as well as validity and reliability to diagnose depression among cancer patients.…”
Section: Discussionsupporting
confidence: 90%
“… 22 , 23 Erstwhile studies conveyed that BDI-II was the gold standard to diagnose depression due its better sensitivity and specificity. 24–27 The literature described that BDI-II has several items on somatic symptoms of depression (such as items about loss of energy, fatigue, and loss of appetite), which may cause an overestimation of positive cases in patient groups with somatic illnesses. 2 , 28 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Healthy adults aged 19 to 65 years with psychological stress and subclinical symptoms of depression or anxiety were recruited by advertising in the hospital and the local community, from October 2018 to August 2019. Enrolled participants underwent screening tests at the first visit (within two weeks prior to initiation of the intervention), and we included those who met both of the following criteria: ( 1 [19], BDI-II [20], and BAI [21] were developed and validated in the Korean population. The exclusion criteria were as follows: (1) psychiatric disorders including mood disorders, anxiety disorders, and psychotic disorders; (2) withdrawal syndrome from alcohol or smoking; (3) history of treatment for stress, depression, and anxiety within four weeks prior to study; (4) any severe stressful life events within four weeks prior to study; (5) use of oral steroids, sleeping pills, anorectic agents, beta-blockers, antibiotics, drugs related to colon diseases, any type of pre-or probiotics including yogurt and other functional foods for stress or insomnia within two weeks; and (6) medical illness such as uncontrolled hypertension, uncontrolled diabetes mellitus, thyroid diseases, and impaired renal or hepatic function.…”
Section: Study Populationmentioning
confidence: 99%
“…This scale has been reported to demonstrate very good sensitivity and specificity [ 38 ]. Higher results indicate a greater severity of depressive symptoms, but there are large variances of cut-off scores for different populations, for instance 7 points for Parkinson’s disease patients or 10 points for depressive disorders in students [ 2 , 39 ]. Some authors suggest 0–12 score as an indicator of a minimal depression [ 40 ].…”
Section: Discussionmentioning
confidence: 99%